PENGARUH PENERAPAN SISTEM INFORMASI KEUANGAN DESA DAN PENGENDALIAN INTERNAL TERHADAP AKUNTABILITAS DANA DESA - Dewi, Putu Ayu Desy Ratna; Julianto, I Putu (Jurnal Akuntansi Profesi, 2020)
Village funds are allocations of the State Revenue and Expenditure Budget directly to the village government. Receiving village funds that are so large has a big risk too, therefore village funds that are received must be accounted for properly, so the village government is required to have good accountability by the central government. This study aims to determine the effect of the village financial information system on the accountability of village fund management and the influence of the Government's internal control system on the accountability of village fund management. The method used in this research is quantitative by using primary data obtained from the questionnaire. The population in this study were all secretaries and treasurers of village government in Buleleng Regency, amounting to 258 people. Based on the results of sample calculations using the Slovin method, from 56 villages in Buleleng Regency, the number of respondents was determined as many as 112 respondents. The data collection technique is done by distributing questionnaires online using google form. Methods of data analysis using multiple linear regression with the help of the SPSS version 24 for Windows program.